Patterns of utilization and clinical adoption of 0.35 Tesla MR-guided radiation therapy in the United States – Understanding the transition to adaptive, ultra-hypofractionated treatments. (January 2023) - Chuong, Michael D.; Clark, Mary Ann; Henke, Lauren E.; Kishan, Amar U.; Portelance, Lorraine; Parikh, Parag J.; Bassetti, Michael F.; Nagar, Himanshu; Rosenberg, Stephen A.; Mehta, Minesh P.; Refaat, Tamer; Rineer, Justin M.; et al.
Highlights: Largest MRgRT utilization study in the United States; 5736 treatment courses. Rapid uptake of SBRT (84.9%) with MRIdian MRgRT by the end of 2020. On-table adaptive radiation therapy used in 51.0% of courses by the end of 2020. Most common tumor sites in 2020: pancreas 23.2%, prostate 18.2%, liver 15.4%, lung 9.7% Abstract: Purpose/Objective: Magnetic resonance-guided radiation therapy (MRgRT) utilization is rapidly expanding worldwide, driven by advanced capabilities including continuous intrafraction visualization, automatic triggered beam delivery, and on-table adaptive replanning (oART). Our objective was to describe patterns of 0.35Tesla(T)-MRgRT (MRIdian) utilization in the United States (US) among early adopters of this novel technology. Materials/Methods: Anonymized administrative data from all US MRIdian treatment systems were extracted for patients completing treatment from 2014 to 2020. Detailed treatment information was available for all MRIdian linear accelerator (linac) systems and some cobalt systems. Results: Seventeen systems at 16 centers delivered 5736 courses and 36, 389 fractions (fraction details unavailable for 1223 cobalt courses), of which 21.1% were adapted. Ultra-hypofractionation (UHfx) (1–5 fractions) was used in 70.3% of all courses. At least one adaptive fraction was used for 38.5% of courses (average 1.7 adapted fractions/course), with higher oART use in UHfx dose schedules (47.7% of courses, average 1.9 adapted fractions per course). The most commonly treated organ sites were pancreas (20.7%), liver (16.5%), prostate (12.5%), breast (11.5%), and lung (9.4%). Temporal trends show a compounded annual growth rate (CAGR) of 59.6% in treatment courses delivered, with a dramatic increase in use of UHfx to 84.9% of courses in 2020 and similar increase in use of oART to 51.0% of courses. Conclusions: This is the first comprehensive study reporting patterns of utilization among early adopters of MRIdian in the US. Intrafraction MR image-guidance, advanced motion management, and increasing adoption of adaptive radiation therapy has led to a substantial transition to ultra-hypofractionated regimens. 0.35 T -MRgRT has been predominantly used to treat abdominal and pelvic tumors with increasing use of on-table adaptive replanning, which represents a paradigm shift in radiation therapy.